Model Pelayanan Pelanggan pada Toko Eceran Tradisional - Panca Wiputra; Ujang Sumarwan; Hari Wijayanto (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Retail Business is growing that makes traditional retail company must compete with modern retail company. It is needed for traditional company to maintain service quality to achieve satisfaction and loyalty. Sinar Fajar is one who keeps traditional retail by delivering goods to smaller retailer company. This research is aim to gives traditional retail company a broad view about which variable that gives impacts for customers satisfaction and the strategy to implicate the result of research.  Service Quality is measured by Retail Service Quality Scale (RSQS) method which is specific to measure service performance in retail industry worldwide. Data was collected from 176 respondent that participate by filling self administered questionnaire after they shop from Sinar Fajar. Research was conducted in January-March 2014 and analyzed with Customers Satisfaction Index (CSI), Structural Equation Modeling (SEM), and Importance Performance Analysis (IPA) Method to advice the company that which variable shows impacts for customers satisfaction. The result is 71.45% Customer is satisfied by the performance of Sinar Fajar, IPA has identified groups of variable to make strategic decision to allocating resources. Variable Dimension that influence most is policy and the least is Personal Interaction. Customers who are satisfied will become loyal so they will recommend Sinar Fajar to other Customers